COMPARISON OF BIODIESEL B-20 AND B-30 ON DIESEL ENGINE PERFORMANCES AND EMISSIONS - Lies Aisyah; Cahyo Setyo Wibowo; Sylvia Ayu Bethari (Testing Center for Oil and Gas LEMIGAS, 2016)
Biodiesel is renewable energy that is made from renewable sources such as vegetable oil (palm oil, soybean oil or jathropa oil) through a trans-esterification reaction. Biodiesel can be used as a substitute for diesel fuel or as a mixture with diesel fuel. B-20 and B-30 fuel are a biodiesel mixture with diesel fuel which contains 20% biodiesel and 80% diesel fuel and 30% biodiesel and 70% diesel fuel respectively. The aim of this study is to compare the performance tests of B-20 and B-30 on a diesel engine. Comparison of their performance comprises engine power, engine torque, specific fuel consumption (SFC) in various loads and emissions. Result shows that the B-20 and B-30 performance is affected by the chemical-physical characteristics of fuel, such as kinematic viscosity, cetane number, density and calorific values. Performance test results show that B-30 has 1.69% lower engine power and 0.62% higher SFC than B-20 at a full load condition. In contrast, B-30 has better emissions than B-20 with a 6.71% decrease in smoke opacity.